Glutamine and Glutamate Reference Intervals as a Clinical Tool to Detect Training Intolerance During Training and Overtraining - Hohl, Rodrigo; Nunes, Lázaro Alessandro Soares; Reis, Rafael Alkmin; Brenzikofer, René; Ferraresso, Rodrigo Perroni; Spindola, Foued Salmen; Macedo, Denise Vaz (IntechOpen, 2012)
None